Computational investigation of a ternary model of SnoN-SMAD3-SMAD4 complex. (December 2019) - Ji, Mingfei; Ding, Yelei; Li, Xiaolong; Mao, Ningfang; Chen, Jie
Graphical abstract: Highlights: A ternary model of SnoN-SMAD3-SMAD4 complex was obtained using MD simulations and molecular modeling methods. The open form of SnoN exists in two, open and semi-closed, conformations. This work can advance our understanding of the ternary SonN-SMAD3-SMAD4 complex in the regulation of TGFβ signaling pathway. Abstract: The transforming growth factor β (TGFβ) plays an essential role in the regulation of cellular processes such as cell proliferation, migration, differentiation, and apoptosis by association with SMAD transcriptional factors that are regulated by the transcriptional regulator SnoN. The crystal structure of SnoN-SMAD4 reveals that SnoN can adopt two binding modes, the open and closed forms, at the interfaces of SMAD4 subunits. Accumulating evidence indicates that SnoN can interact with both SMAD3 and SMAD4 to form a ternary SnoN-SMAD3-SMAD4 complex in the TGFβ signaling pathway. However, how the interaction of SnoN with the SMAD3 and SMAD4 remains unclear. Here, molecular dynamics (MD) simulations and molecular modeling methods were performed to figure out this issue. The simulations reveal that SnoN open exists in two, open and semi-closed, conformations. Molecular modeling and MD simulation studies suggest that the SnoN closed form interferes with the SMAD3-SMAD4 protein; in contract, the SnoN open can form a stable SnoN-SMAD3-SMAD4 complex. These mechanistic mechanisms may help elucidate the detailed engagement of SnoN with two SMAD3 and SMAD4 transcriptional factors in the regulation of TGFβ signaling pathway.